THEORETICAL-METHODOLOGICAL FRAMEWORK OF ANALYSIS OF ALBANIAN PUBLIC DISCOURSES ОN SERBIAN SACRED MONUMENTS IN KOSOVO AND METOHIA - Pešić, Milena (Serbian political thought, 2024)
Starting from the idea of ​​identity coding of these discourses, the research is, on the one hand, aimed at considering the construction of the so-called “Kosovo identity” as a component of “national, state policy“, that is, the branding of the so-called Kosovo state/nation. The second analytical focus of the research is the deconstruction of the cultural and historical markers of Serbian identity embodied in the most significant Serbian sacred monuments in Kosovo and Metohija. For the purposes of the analysis, the analytical model of national identity discourse construction, created within the discursive-historical approach to critical discourse analysis, was adopted. The key theoretical concept of strategy is a kind of synthesis of strategy categories from the mentioned model, and some categories of political discourse strategies are operationalized into analytical tools of our research. The used methodology provided the possibility of concrete insights into what kind of global discursive and linguistic strategies and argumentative schemes, and in which relevant contexts, public Albanian discourses about Serbian sacred monuments in Kosovo and Metohija achieve their constructive effects related to the so-called “Kosovo identity”, that is, those deconstructive ones, related to the Serbian identity. The paper’s main contribution is providing a reference framework for the conceptual and analytical linking of discourses on cultural heritage and identity discourses in the context of a certain political agenda. It is about the context of the Albanian policy of denying the Serbian identity in Kosovo and Metohija, i.e., appropriating the Serbian cultural heritage, with the aim of establishing the identity of the pseudo-state creation of Kosovo. By operationalizing the concept of strategy for the analysis of discourse on cultural heritage, an analytical model is offered, which, starting from textual, linguistic, and argumentative analysis, exposes manipulative mechanisms for the discursive realization of political goals, primarily in the field of identity politics.